DETERMINATION OF THE FLOODING ZONE DURING A DAM BREAKS USING THE VOF METHOD BY NUMERICAL SIMULATION - Issakhov, А.; Rakhymzhanova, Ж.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In this paper, we investigated the problem of dam breakage. The authors studied this problem using numerical modeling based on the Navier-Stokes equations with a turbulent k-epsilon RNG model and used the Volume of Fluid (VOF) method and the PISO algorithm. To verify the numerical model, the authors used the test problem of dam break in a 450 channel. The simulation results were compared with experimental data and with numerical data of another author. Having convinced of the correctness of the mathematical model, the authors carried out a numerical simulation of the main problem in three versions: without barriers, with one obstacle, with two obstacles. As the obstructions restrained the flow, a decrease in the water level and a slower time for the appearance of water could be observed. The main goal of this work is to analyze the flow in a channel with complex turn reliefs.